Effect of pH Changes on Antioxidant Capacity and the Content of Betalain Pigments During the Heating of a Solution of Red Beet Betalains - Mikołajczyk-Bator Katarzyna; Czapski Janusz (Polish Journal of Food and Nutrition Sciences)
Red beets and their products are mainly consumed after processing. In this study, the effect of pH on changes in antioxidant capacity (AC) and the content of betalain pigments were analysed during the heating of a betalain preparation solution. With pH ranging from 4 to 9 during the heat-treatment, the content of red pigments decreased depending on the pH level of the sample. The losses of red pigments in the investigated betalain preparation solution increased along with rising pH levels of the heated solution. The greatest losses were recorded at pH of 9.0. An opposite correlation was observed for yellow pigments. The content of yellow pigments in the heated betalain preparation solution was increasing along with increasing pH. The most pronounced increase in the content of yellow pigments was found at pH of 6.5 and 7.0. At the same time, the heated betalain preparation solution was shown to exhibit a higher antioxidant capacity at pH of 6.0 (14.9 μmol Trolox/mL) than at pH of 4.0 (12.6 μmol Trolox/mL). It was observed that the increase in the antioxidant capacity in heated betalain preparation solutions with pH in the 6.0–6.5 range occurred as a result of increased concentrations of neobetanin, assessed by HPLC, within the pH range from 5.0 to 6.5.